2020
DOI: 10.1016/j.vas.2020.100146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-slaughter factors on welfare of broilers

Abstract: Pre-slaughter factors adversely affecting bird welfare were studied at the slaughterhouse. The incidence of dead on arrival (DoA), bruises and dehydration was investigated in 64 different mixed-sex batches of broilers coming from 64 different farms rearing fast-growing genotypes (Ross or Cobb). The effects of catching team, method of catching, time of day for catching and transport, density per cage, transport duration, transport distance, lairage duration and water withdrawal were considered. The average DoA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
(59 reference statements)
1
24
0
2
Order By: Relevance
“…Jacobs et al [ 11 ] found that catching at the farm had a significant effect on the incidence of wing fractures in broilers (the difference in prevalence at the farm and after catching was 0.12% and 1.88%, respectively, and rose to a mean of 1.95% post mortem, which could include machine damage). In addition, when evaluating the factors that influenced the incidence of bruising in broilers at slaughterhouses, Saraiva et al [ 12 ] and Langkabel et al [ 8 ] observed the most bruising on wings. On the other hand, Gouveia et al [ 49 ] observed more bruising on the body (pectoral musculature) than the legs and/or wings, which was probably due to increased injuries caused by untrained personnel on the openings of transport containers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobs et al [ 11 ] found that catching at the farm had a significant effect on the incidence of wing fractures in broilers (the difference in prevalence at the farm and after catching was 0.12% and 1.88%, respectively, and rose to a mean of 1.95% post mortem, which could include machine damage). In addition, when evaluating the factors that influenced the incidence of bruising in broilers at slaughterhouses, Saraiva et al [ 12 ] and Langkabel et al [ 8 ] observed the most bruising on wings. On the other hand, Gouveia et al [ 49 ] observed more bruising on the body (pectoral musculature) than the legs and/or wings, which was probably due to increased injuries caused by untrained personnel on the openings of transport containers.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include duration of catching and time of the day of the catching, where positive correlation was found between the prevalence of wing fractures and duration of catching and loading, and the risk of bruising also increased when birds were loaded at night [ 11 ]. Conversely, Saraiva et al [ 12 ] observed a higher percentage of bruising when birds were caught before midnight and Nijdam et al [ 10 ] observed more bruising in broilers transported during the day than at night. The process of hanging and stunning increases the prevalence of traumatic wing injuries due to wing flapping and consequent wing injuries [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that the high per crate density during transport increases the bruises percentage (3.37%) in broilers. 4 On processing plants from receiving to post-slaughter, injuries may occur, which may raise the reject rates of birds or their meat. 21 All these bruises, traumas, wing and leg dislocations, sternum, and other bone fractures result welfare concerns to chickens, rising reject rates and ultimately economic loss.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various on-farm and pre-slaughter risk factors involved in the death of the birds are reported as the flock size, sex, age, on-farm mortality and culling, feed withdrawal and previous pathological condition, catching day, catching time, catching method, stocking density and size, vehicle, transportation time, season, environmental condition, transportation and lairage duration. [2][3][4] Many conditions during transportation are critical risk factors, and a chicken's death is a response to these vital conditions. Thermal conditions during transportation have primary concern and drop the survival percentage of the transported poultry.…”
Section: Introductionmentioning
confidence: 99%